A New Pathogenic Missense Variant in a Consanguineous North-African Family Responsible for a Highly Variable Aceruloplasminemia Phenotype: A Case-Report - Lobbes, Hervé; Reynaud, Quitterie; Mainbourg, Sabine; Savy-Stortz, Claire; Ropert, Martine; Bardou-Jacquet, Edouard; Durupt, Stéphane (Frontiers in Neuroscience, 2022)
Aceruloplasminemia is a rare recessive inherited disorder. Mutations in the ceruloplasmin gene cause depressed ferroxidase activity leading to iron accumulation. The clinical phenotype is highly variable: anemia, retinopathy, diabetes mellitus, psychiatric disorders, and neurological symptoms including parkinsonian disorders and dementia are the main features of this disease. Characterized by high serum ferritin with low transferrin saturation, aceruloplasminemia uniquely combines brain, liver and systemic iron overload. We report here four new cases of aceruloplasminemia in a consanguineous North-African family. Genetic sequencing revealed a homozygous missense variant c.656T>A in exon 4 of the ceruloplasmin gene activity which had been described previously as of “unknown significance” in the dbSNP database and never associated with ACP in the HGMD database. Ferroxidase activity was strongly depressed. Clinical manifestations varied among cases. The proband exhibited mild microcytic anemia, diabetes mellitus, psychosis and parkinsonism, whereas the other cases were asymptomatic or mildly anemic, although high serum ferritin and brain iron deposition were documented in all of them. Therapeutic management was complex. The proband started treatment when already symptomatic and he rapidly declined. In the asymptomatic cases, the treatment was associated with poor tolerance and was discontinued due to anemia requiring red blood cell transfusion. Our series illustrates the need for new therapeutic approaches to aceruloplasminemia.